The 1.78-kb insertion in the 3′-untranslated region of RXFP2 does not segregate with horn status in sheep breeds with variable horn status. Issue 1 (December 2016) - Lühken, Gesine; Krebs, Stefan; Rothammer, Sophie; Küpper, Julia; Mioč, Boro; Russ, Ingolf; Medugorac, Ivica
Abstract Background The mode of inheritance of horn status in sheep is far more complex than a superficial analysis might suggest. Observations, which were mostly based on crossbreeding experiments, indicated that the allele that results in horns is dominant in males and recessive in females, and some authors even speculated about the involvement of more than two alleles. However, all recent genome-wide association analyses point towards a very strong effect of a single autosomal locus on ovine chromosome 10, which was narrowed down to a putatively causal insertion polymorphism in the 3′-untranslated region of therelaxin/insulin-like family peptide receptor 2 gene (RXFP2 ). The main objective of this study was to test this insertion polymorphism as the causal mutation in diverse sheep breeds, including breeds with a variable and/or sex-dependent horn status. Results After re-sequencing a region of about 246 kb that covered theRFXP2 gene and its flanking regions for 24 sheep from six completely horned and six completely polled breeds, we identified the same insertion polymorphism that was previously published as segregating with horn status in these breeds. Multiplex PCR genotyping of 489 sheep from 34 breeds and some crosses between sheep breeds showed a nearly perfect segregation of the insertion polymorphism with horn status in sheep breeds of Central and Western European origin. In these breeds and their crossings, heterozygous males were horned and heterozygous females were polled. However, this segregation pattern was not, or at least not completely, reproducible in breeds with sex-dependent and/or variable horn status, especially in sheep that originated from even more southern European regions and from Africa. In such breeds, we observed almost all possible combinations of genotype, sex and horn status phenotype. Conclusions The 1.78-kb insertion polymorphism in the 3′-untranslated region ofRXFP2 and SNPs in the 3′-UTR, exon 14 and intron 11 of this gene that we analyzed in this study cannot be considered as the only cause of polledness in sheep and are not useful as a universal marker to define the genetic horn status in sheep.